Experimental and numerical studies on dynamic performance of the rotating composite sandwich panel with CNT reinforced MR elastomer core. (1st December 2021) - Selvaraj, Rajeshkumar; Ramamoorthy, Manoharan; Arumugam, Ananda Babu
Abstract: The work presented in this paper is focused on the investigation of vibration and damping characteristics of the rotating laminated composite hybrid MR elastomer sandwich panel. The laminated composite hybrid MR elastomer sandwich panel contains the constraining and base layers made of composite laminates and the core layer made of carbon nanotubes reinforced magnetorheological elastomer (hybrid MR elastomer). Higher-order shear deformation theory (HSDT) and finite element (FE) formulations are employed to derive the governing equations of the laminated composite hybrid MR elastomer sandwich panel. The performance of the derived numerical model is validated by comparing the results evaluated using experimental investigations on the prototype of laminated composite MR elastomer and hybrid MR elastomer sandwich panels under various rotating speeds. The influence of rotating speed, magnetic field, core-face sheet thickness ratio, ply orientations and support conditions on the dynamic properties of hybrid MR elastomer sandwich panel are explored. Also, the forced vibrations of the laminated composite hybrid MR elastomer sandwich panel are examined at different magnetic fields. Further, it can be observed that the reinforcement of CNTs in MR elastomer significantly influences the natural frequencies, loss factors, mode shapes and transverse displacements of the composite sandwich panels. This research work provides the guidelines for the researchers/designers on improving the dynamic properties and reduces the transverse vibrations of composite sandwich structures using the reinforcement of CNTs in smart materials.